Методи підвищення рівня лояльності студентів технічного університету до ВНЗ - Боровинська, Ю. Д. (ХНУРЕ, 2021)
Loyalty is an acceptance, a positive attitude of a person towards something specific. Personnel loyalty means a benevolent, correct, sincere, respectful attitude towards management, other persons, their actions and the company as a whole. The level of student loyalty to a university is an important factor in its competitiveness, since in this way the university enhances its attractiveness not only to applicants, but also to employers, investors and the state, which can provide it with additional subsidies, and serves as a topical issue. Loyalty formation is influenced by university stability, corporate culture, motivation, career orientation, work beliefs, spontaneity and tolerance for uncertainty.
Keywords: філософія; ВНЗ